New perspective in diagnostics of mitochondrial disorders: two years' experience with whole-exome sequencing at a national paediatric centre. Issue 1 (December 2016) - Pronicka, Ewa; Piekutowska-Abramczuk, Dorota; Ciara, Elżbieta; Trubicka, Joanna; Rokicki, Dariusz; Karkucińska-Więckowska, Agnieszka; Pajdowska, Magdalena; Jurkiewicz, Elżbieta; Halat, Paulina; Kosińska, Joanna; Pollak, Agnieszka; Rydzanicz, Małgorzata; et al.
Abstract Background Whole-exome sequencing (WES) has led to an exponential increase in identification of causative variants in mitochondrial disorders (MD). Methods We performed WES in 113 MD suspected patients from Polish paediatric reference centre, in whom routine testing failed to identify a molecular defect. WES was performed using TruSeqExome enrichment, followed by variant prioritization, validation by Sanger sequencing, and segregation with the disease phenotype in the family. Results Likely causative mutations were identified in 67 (59.3 %) patients; these included variants in mtDNA (6 patients) and nDNA: X-linked (9 patients), autosomal dominant (5 patients), and autosomal recessive (47 patients, 11 homozygotes). Novel variants accounted for 50.5 % (50/99) of all detected changes. In 47 patients, changes in 31 MD-related genes (ACAD9, ADCK3, AIFM1, CLPB, COX10, DLD, EARS2, FBXL4, MTATP6, MTFMT, MTND1, MTND3, MTND5, NAXE, NDUFS6, NDUFS7, NDUFV1, OPA1, PARS2, PC, PDHA1, POLG, RARS2, RRM2B, SCO2, SERAC1, SLC19A3, SLC25A12, TAZ, TMEM126B, VARS2 ) were identified. TheACAD9, CLPB, FBXL4, PDHA1 genes recurred more than twice suggesting higher general/ethnic prevalence. In 19 cases, variants in 18 non-MD related genes (ADAR, CACNA1A, CDKL5, CLN3, CPS1, DMD, DYSF, GBE1, GFAP, HSD17B4, MECP2, MYBPC3, PEX5, PGAP2, PIGN, PRF1, SBDS, SCN2A ) were found. The percentage of positive WES results rose gradually with increasing probability of MD according to the Mitochondrial Disease Criteria (MDC) scale (from 36 to 90 % for low and high probability, respectively). The percentage of detected MD-related genes compared with non MD-related genes also grew with the increasing MD likelihood (from 20 to 97 %). Molecular diagnosis was established in 30/47 (63.8 %) neonates and in 17/28 (60.7 %) patients with basal ganglia involvement. Mutations inCLPB, SERAC1, TAZ genes were identified in neonates with 3-methylglutaconic aciduria (3-MGA) as a discriminative feature. New MD-related candidate gene (NDUFB8 ) is under verification. Conclusions We suggest WES rather than targeted NGS as the method of choice in diagnostics of MD in children, including neonates with 3-MGA aciduria, who died without determination of disease cause and with limited availability of laboratory data. There is a strong correlation between the degree of MD diagnosis by WES and MD likelihood expressed by the MDC scale.